Asymptomatic Supraventricular Arrhythmias in Patients Undergoing Dialysis - O. V. Likhachev-Mishchenko; A. A. Kornienko; N. A. Kornienko; L. A. Khaisheva; A. A. Dyuzhikov; S. V. Shlyk (Столичная издательская компания, 2021)
Aim. Supraventricular arrhythmias (SVA) are associated with high morbidity and mortality. However, little attention is paid to this condition in patients undergoing hemodialysis. The aim of this study was to analyze the long-term relationship of intradialytic SVA, including asymptomatic arrhythmias, with adverse events in a cohort of patients undergoing hemodialysis.Material and methods. An observational prospective study was conducted in a group of patients on hemodialysis with a 10-year follow-up. The study involved 77 patients (42 men and 35 women; mean age 58±15 years) with sinus rhythm, then they were monitored for ECG for six consecutive hemodialysis sessions during recruitment.Results. Arterial hypertension was present in 68.8% of patients, diabetes mellitus in 29.9% of patients. SVA were reported in 38 patients (49.3%); they all had a short-term, asymptomatic character and were terminated independently. Age (hazard ratio [HR] 1.04 per year; 95% confidence interval [CI] 1.00-1.08) and an increase of the atrium (HR 4.29; 95%CI 1.30-14.09) were associated with supraventricular arrhythmia in multidimensional analysis. During an average follow-up of 40 months, 57 patients died, and cardiovascular diseases were the main cause of death (52.6%). Variables associated with all-cause mortality in the Cox model were age (HR 1.04 per year; 95%CI 1.00-1.08), C-reactive protein (HR 1.04 per 1 mg/l; 95%CI 1.00-1.08) and supraventricular arrhythmias (HR 3.21; 95%CI 1.29-7.96). Patients with supraventricular arrhythmias also had a higher risk of nonfatal cardiovascular events (HR 4.32; 95%CI 2.11-8.83) and symptomatic atrial fibrillation during observation (HR 17.19; 95%CI 2.03-145.15).Conclusions. Strong relationships have been established between the presence of supraventricular arrhythmias recorded during ECG during dialysis and symptomatic AF developing in the future. Patients with supraventricular arrhythmias had a larger right atrium. Age and supraventricular arrhythmias are the main variables associated with mortality in dialysis patients.